AEROBIC BACTERIAL PROFILE AND ANTIBIOGRAM OF BRONCHOALVEOLAR LAVAGES IN PULMONARY INFECTIONS AT A TERTIARY CARE HOSPITAL - M., SRIVALLI; S., SWAPNA; P., RATNA KUMARI; P., KAMALA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Lower respiratory tract infections (LRTIs) are one of the common clinical problems in community and hospital settings and the commonest causes of morbidity and mortality. In pulmonary infections, BAL fluid sample has high sensitivity and reliability in diagnosis. To determine the distribution of bacterial isolates in BAL samples and antibiotic sensitivity patterns in most frequently isolated bacterial pathogens other than Mycobacterium tuberculosis. Methods: The study was conducted on 218 BAL samples received in the microbiology laboratory, Andhra Medical College from various wards of King George Hospital; Visakhapatnam; Andhra Pradesh, over a period of one year (from January 2022 to December 2022). All samples were processed according to standard microbiology protocols. Antimicrobial susceptibility was tested by the Kirby-Bauer disc diffusion method as per the CLSI guidelines 2022. Results: Total 218 BAL samples were studied. Among 218 BAL samples, 144(66%) samples were from male patients and 74(34%) samples from female patients. Out of 218 samples, 119(55%) were culture positive and 99(45%) were culture negative. Among 119 bacterial isolates, most predominant pathogen was Klebsiella pneumoniae 51(42.8%) followed by Pseudomonas aeruginosa 46(38.6%), Escherichia coli 11(9.2%), Enterobacter species 6(5.0%), Acinetobacter species 3(2.5%) and Staphylococcus aureus 2(1.68%). Out of these isolated pathogens, Gram-negative bacilli were more. These gram-negative isolates were most sensitive to Piperacillin-Tazobactam (74.3%) followed by Meropenem (71.7%), Amikacin (60.6%) and least sensitive to Ceftazidime (39.3%) and Cefotaxime (37.6%). Conclusion: The present study shows that gram-negative bacilli were more commonly isolated in BAL samples and the bacterial isolates were most sensitive to Piperacillin-Tazobactam and Meropenem and highly resistance to Cefotaxime and Ceftazidime. Hence, formulating a regular antibiogram in hospitals will help in developing local antibiotic policies, which may provide better patient management and judicious use of antibiotics by clinicians to prevent the risk of the emergence of multidrug-resistant pathogens.